Galectin-3 is required for the microglia-mediated brain inflammation in a model of Huntington’s disease - Jian Jing Siew (Nature Portfolio, 2019)
The authors show that Galectin-3 is up–regulated in brain tissues from patients and a mouse model of Huntington’s disease (HD) and correlates with disease severity. Galectin-3 accumulates at damaged lysosomes in HD microglia, prevents the clearance of damaged lysosomes, and promotes inflammation.